Cross professional team characteristics, translation and construct validation of teamwork survey questionnaire (TSQ) at Malaysian east coast public Hospital - Samsudin, Wan Siti Auni Wan (2023)
Cross professional teamwork in healthcare refers to the interaction between individuals with different expertise and training backgrounds, working together towards shared patient care goals. Cross professional teamwork is necessary to support integrated service delivery. However, cross professional teamwork has not been given sufficient attention in Malaysia’s developing country context. There is a lack of tools to assess cross professional teamwork for Malaysian settings. This study aimed to translate the English version teamwork survey questionnaire (TSQ) into Malay and perform tool construct validation at a Malaysian east coast public hospital. The TSQ assesses teamwork on domains of integration, climate and efficiency; the tool has been previously used in Swedish and Australian settings. This study’s aim was achieved through a cross-sectional mixed methods study in three phases. Phase 1 and Phase 2 were carried out through qualitative approaches while Phase 3 utilized a quantitative approach. Phase 1 focused on translating the TSQ into Malay language using forwardbackward translation together with the committee approach. Next, a qualitative interview study was conducted in Phase 2 to explore fulfillment of cross professional team characteristics at the hospital’s 16 inpatient wards. A total of 35 interviews were conducted with medical, nursing and allied health professionals; the sample is sufficient for qualitative data saturation. Recordings from interview sessions were transcribed and thematically analyzed. The construct validity and reliability of the Malay version TSQ was determined in Phase 3. In Phase 3, 150 respondents were recruited from wards found to have cross professional team characteristics during Phase 2. A response rate of 98.24% was obtained in filling in the Malay version TSQ, the percentage of recruited respondents being sufficient for statistical analysis. Construct validity was assessed through Principal Component Analysis with Varimax rotation and reliability was tested through the analysis of internal consistency. Findings from Phase 1 indicate the translated Malay version TSQ to have equivalence with the English version. Phase 2 interview findings reveal that inpatient wards generally fulfill cross professional team criteria related to team composition, patient care objectives and professional interactions. Phase 3 construct validation results indicate that three constructs namely team climate, team efficiency and team integration, without any item deletion are valid for the Malay version TSQ. The Cronbach’s alpha value is 0.917 for the translated whole TSQ scale, while the three scale constructs also have reliable Cronbach’s alpha values in the range of 0.703-0.946. Discrepancies for particular words used from the forward backward translation process were resolved without affecting meaning of the original items. Health professionals in this study acknowledge the different professions involved in patient care. However, disciplinary diversity at the respective wards varies depending on patient care specialties and treatment objectives. The Cronbach’s alpha values for the Malay version TSQ factors reflect better team climate and integration values and comparably similar team efficiency value when contrasted with the original tool. In conclusion, the results support usage of the tool as a reliable instrument for assessing cross professional teams in other similar Malaysian public healthcare services. Further research could test the reliability and validity of the Malay version TSQ in other Malaysian regions.